PENGARUH FINANCIAL DISTRESS, DEBT DEFAULT, DAN AUDIT TENURE TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2017 - priska liliani (Jurnal Bina Akuntansi, 2021)
Manufacturing companies are a sector that is quite important for the development of the country's economy. In Indonesia, there are more companies in the manufacturing sector listed on the Indonesia Stock Exchange (IDX). With this larger number of companies, companies in the manufacturing sector have significant industrial influence as well as significant stock fluctuations on the IDX. The purpose of this study aims to analyze the effect of financial distress, debt default, and audit tenure on going concern audit opinion. To support this research, the author uses a sample of manufacturing companies listed on the Stock Exchange as the object of research. From the results of observations for 3 years, namely from 2015 - 2017, 28 samples were obtained to be studied according to the observation period so that the number of units of analysis was equal to 84. Based on tests carried out using logistic regression, empiricalevidence was obtained that the financial distress variable had a positive influence. which is significant to the acceptance of going concern audit opinion. The debt default variable has no significant effect on the going concern audit opinion acceptance. The Audit Tenure variable does not have a significant effect on the going concern audit opinion acceptance.